The Club-Level Road Cyclist: Injury, Pain, and Performance. Issue 2 (March 2015) - Dahlquist, Miriah; Leisz, Marie-Christine; Finkelstein, Marsha
Abstract : Objective: The aims of this study were to (1) examine riding habits of injured cyclists, (2) identify factors related to seeking medical treatment, (3) investigate performance of recreational road cyclists compared with established norms regarding strength and flexibility measures, and (4) propose cycling-specific injury risk factors. Design: Observational and prospective study. Setting: Cycling store and bicycle distribution company. Participants: Sixty-three experienced road cyclists. Assessment of Risk Factors: Initial data collection included a questionnaire. A 2-week training diary and 8 weekly follow-up injury questionnaires were also collected. Main Outcome Measures: Training habits and injury history, bike fit, flexibility, and isometric, dynamic, and plyometric strength measures. Results: Participants were likely to have an injury at baseline, and chronic pain was common. Cyclists trained for an equal quantity of time irrespective of experiencing pain. Injury severity in terms of pain level and participant age were factors in seeking medical care. Our participants performed poorly on our testing protocol compared with available norms. Flexibility, strength, and bike fit measures did not predict injury. Previous injury predicted prospective injury. The knee and lumbar region were most frequently injured. Conclusions: Cycling is a sport in which injury risk and prevention need to be further studied. Cyclists are frequently injured but continue to participate in cycling at volumes equal to their healthy peers. Clinical Relevance: This study outlines a clinically reproducible cyclist assessment and discusses behaviors common to the cycling patient.